The Last Broadcast: Reflections on the life and legacy of BBC Four. (June 2022) - Weston, Leanne; Samuel, Michael
Following the news detailed in the BBC Annual Plan 2021/22 that BBC Four will cease to broadcast original content and will revert to an archive-only channel as a cost-cutting measure, this article endeavours to understand the legacy of the channel as it was, as it is and what it could become.